Compaction influence on spring-in of thin composite parts: Experimental and numerical results. (July 2015) - Sorrentino, L; Bellini, C
Geometric unconformities may arise due to residual stresses during the manufacturing process of polymer matrix composite materials. Compaction of the laminate, due to resin squeeze, is another phenomenon that occurs and it influences the mechanical behaviour of the laminate itself. In the past, models for spring-in or for compaction were developed separately, whereas in the present work a new kind of analysis is developed to take into account both residual stresses and compaction that take place during cure simultaneously. This analysis is composed by two different steps: in the former the compaction is predicted, in the latter the cure state and the residual stress condition are determined. Finally, the relationship between different degrees of compaction and the corresponding values of spring-in is studied, and it was found that a higher value of thickness reduction produces the smallest residual stresses for the composite structures with angled cross sections.